Objects, Models, Components, Patterns 50th International Conference, TOOLS 2012, Prague, Czech Republic, May 29-31, 2012. Proceedings - Furia, Carlo A.; Nanz, Sebastian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 50th International Conference on Objects, Models, Components, Patterns, TOOLS Europe 2012, held in Prague, Czech Republic, during May 29-31,2012. The 24 revised full papers presented were carefully reviewed and selected from 77 submissions. The papers discuss all aspects of object technology and related fields and demonstrate practical applications backed up by formal analysis and thorough experimental evaluation. In particular, every topic in advanced software technology is adressed the scope of TOOLS.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Programming Techniques; Mathematical Logic and Formal Languages; Computer Communication Networks